Punicalagin Mollifies Lead Acetate-Induced Oxidative Imbalance in Male Reproductive System - Rao, Faiza (Int J Mol Sci, 2016)
Punicalagin (PU) is a known antioxidant. The present study examined PU to protect against lead-induced oxidative stress (OS) testicular damage in mice. Significant increase in lipid peroxidation (LPO) after intraperitoneal injection of lead acetate (LA) indicated enormous generation of reactive oxygen species (ROS). Lead-induced OS has a direct effect on the differentiation of spermatogonial cells, showing a significant decline in sperm count. Supplementation of PU significantly changes values of LPO and glutathione (GSH) with a concomitant increase in sperm count, a marked decrease in the abnormal sperms, and a decline in the morphologically abnormal sperm population. Moreover, the histopathological evaluation of testes and epididymides showed severe changes in mice treated with LA. PU significantly induced nuclear factor erythroid-2 related factor 2-like 2 (Nrf2) expression and phase II enzymes, and data suggest that PU may inhibit OS through Nrf2 activation. The fertility test proved that PU might play an important role in male infertility treatment, especially in the type of infertility induced by OS.